Evidence of SARS-CoV-2 Transmission Through the Ocular Route - Qu JY (Dove Medical Press, 2021)
Jing-Yu Qu, Hua-Tao Xie, Ming-Chang Zhang Department of Ophthalmology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of ChinaCorrespondence: Ming-Chang Zhang; Hua-Tao XieDepartment of Ophthalmology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277 Jiefang Avenue, Wuhan, Hubei Province, 430022, People’s Republic of ChinaTel +86-27-85726662Email mingchangzhang@hotmail.com; huataoxie@hust.edu.cnPurpose: Currently, the coronavirus disease 2019 (COVID-19) pandemic is raging around the world. However, the transmission of its pathogen, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), is not fully clear. It is still controversial whether the ocular transmission of SARS-CoV-2 exists. This review aimed to summarize the evidence of SARS-CoV-2 ocular transmission.Methods: Online articles were searched till October 23, 2020 in Pubmed, Embase, and websites of World Health Organization, Centers for Disease Control and Prevention COVID-19, American Academy of Ophthalmology, and American Society of Cataract and Refractive Surgery under the search strategy of ((((“COVID-19”[Mesh]) OR (“SARS-CoV-2”[Mesh])) OR (2019 novel coronavirus)) OR (2019-nCoV)) AND ((((“Conjunctivitis”[Mesh]) OR (Ocular Surface)) OR (“Eye”[Mesh])) OR (“Ophthalmology”[Mesh])). The language was not restricted. After screening, 1445 records were excluded and 168 references original articles were finally included.Results: Cells of ocular surface express both the receptor of angiotensin-converting enzyme 2 (ACE2) and transmembrane serine protease 2 (TMPRSS2), offering molecular bases for the ocular susceptibility to SARS-CoV-2. Accumulated COVID-19 patients presented conjunctivitis as the initial or the only symptom. Whether COVID-19 patients had ocular symptoms or not, SARS-CoV-2 was detectable on the ocular surface, and the isolated virus was infectious, proving that the ocular surface can not only be a reservoir but also a source of contagion. SARS-CoV-2 may reach the ocular surface by hand-eye contact and aerosols. Once SARS-CoV-2 reaches the ocular surface, it may transfer to other systems through the nasolacrimal system or hematogenous metastasis.Conclusion: The ocular surface can serve as a reservoir and source of contagion for SARS-CoV-2. SARS-CoV-2 can be transmitted to the ocular surface through hand-eye contact and aerosols, and then transfer to other systems through nasolacrimal route and hematogenous metastasis. The possibility of ocular transmission of SARS-CoV-2 cannot be ignored.Keywords: COVID-19, SARS-CoV-2, ocular transmission, conjunctivitis, ACE2, TMPRSS2